Electrical stimulation in special clinical situations - van der Steld, Lenises de Paula (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Introduction: Neuromodulation is an approach used to treat diseases that are refractory to clinical treatments by employing electrical and chemical stimulation techniques, especially in cardiac, neurological, and psychiatric disorders. Objective: This study aims to provide an overview of the latest developments in neuromodulation therapies that use electrical stimulation. Methods and results: The present study describes the most common neuromodulation techniques. Neuroplasticity is used to adjust the ions and neural excitability in response to central and peripheral nervous system stimulation. The spinal cord, dorsal root, and gastric stimulations are effective treatments for neuropathies, chronic pain, muscle spasticity, epilepsy, depression, cluster headaches, heart failure, and gastroparesis symptoms. Deep brain stimulation and invasive cortical stimulation are medical procedures used selectively to treat Parkinson’s disease, dystonia, obsessive-compulsive disorder, and chronic pain. Barostimulation therapy is beneficial in controlling refractory hypertension, reducing the risk of cardiovascular events, and improving overall quality of life. Repetitive Transcranial Magnetic Stimulation is a recommended treatment option for fibromyalgia, neuropathic pain, chronic headaches, treatment-resistant depression, generalized anxiety disorders, schizophrenia, and attention deficit disorder. While controlling obesity shows promise in regulating appetite and promoting satiety, more research is needed to understand the safety and efficacy of these therapies in various groups. Conclusion: Neuromodulation devices hold promise for treating diseases that do not respond to clinical treatments. Additional clinical trials and studies are required to understand it fully.